2014
DOI: 10.1159/000368391
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Control Study on the Procedure for Switching Epoetin Beta (EPO) to Epoetin Beta Pegol (CERA) in the Treatment of Renal Anemia in Maintenance Hemodialysis Patients

Abstract: Background/Aims: We investigated the method of switching EPO to CERA that does not cause a decrease in the Hb level. Methods: Fifty EPO-treated patients were randomly divided into two groups in which CERA was administered every two weeks (Q2W) or every four weeks (Q4W). After 8 weeks of treatment, the frequency of administration was changed to Q4W in the former. Follow-up was performed for 24 weeks. Results: There was no difference in the Hb level between the two groups until 6 weeks. In the Q2W group, the Hb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…The reasons for this were reported as follows: (1) it takes 6 weeks for the serum CERA level to stabilize, as shown by a Japanese clinical study [96], and (2) it takes approximately 12 weeks for the dose of CERA administered once every 4 weeks to stabilize after switching from rHuEPO [97]. Moreover, Toida et al compared the efficacy of CERA administered once every 2 weeks after switching from rHuEPO with that of CERA administered once every 4 weeks after switching from rHuEPO in a RCT [98]. They reported that the Hb level decreased in patients who were administered CERA once every 4 weeks, while an optimal Hb level was maintained stably in those administered CERA once every 2 weeks.…”
Section: (2)target Hb Levels To Be Maintained In Pd Patientsmentioning
confidence: 99%
“…The reasons for this were reported as follows: (1) it takes 6 weeks for the serum CERA level to stabilize, as shown by a Japanese clinical study [96], and (2) it takes approximately 12 weeks for the dose of CERA administered once every 4 weeks to stabilize after switching from rHuEPO [97]. Moreover, Toida et al compared the efficacy of CERA administered once every 2 weeks after switching from rHuEPO with that of CERA administered once every 4 weeks after switching from rHuEPO in a RCT [98]. They reported that the Hb level decreased in patients who were administered CERA once every 4 weeks, while an optimal Hb level was maintained stably in those administered CERA once every 2 weeks.…”
Section: (2)target Hb Levels To Be Maintained In Pd Patientsmentioning
confidence: 99%
“…Some reports described the superiority of biweekly CERA administration over monthly administration in that biweekly administration could maintain Hb levels using a lower overall CERA dose. 8 , 9 , 10 , 11 It is noteworthy that biweekly CERA administration maintained ferritin and hepcidin, a negative regulator of iron uptake in the small intestine and iron release from macrophages, at lower levels for 4 weeks after administration than monthly administration. 12 , 13 This result suggested that biweekly administration is advantageous for absorption and iron utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Although conversion to CERA with intervals of once every 2 weeks (Q2W) or 4 weeks (Q4W) from other ESAs is achieved safely in hemodialysis patients and oncemonthly administration is recommended in Japan, the optimal interval of CERA administration is not known. Recently, it is reported that more continuous erythropoiesis was achieved with a Q2W administration of CERA than Q4W [7], and Q2W administration of CERA is more effective than Q4W to achieve target hemoglobin (Hb) levels [8]. Although we also reported more effective erythropoiesis of CERA by Q2W than Q4W, the fluctuation of Hb levels during Q4W is greater than that during Q2W [9], which makes it difficult to compare the true effect of the interval of CERA administration on Hb levels.…”
Section: Introductionmentioning
confidence: 70%
“…Although the precise mechanisms are not clear, in hemodialysis patients, ESA administration exerts a biphasic pattern of serum hepcidin-25 levels; early upregulation followed by late downregulation [14], and low serum hepcidin levels Variables are represented as mean ± standard deviation HD hemodialysis, BUN blood urea nitrogen, Cr creatinine, TP total protein, Alb albumin, Hb hemoglobin, CRP C-reactive protein, Fe iron facilitate iron utilization, which results in a decrease of serum ferritin levels. The degree of iron utilization and recruitment to the hematopoietic system seems to differ according to the type of ESAs [14][15][16] and interval of dosing [7,8]. Transient reduction of serum hepcidin and ferritin levels induced by CERA administration reach a maximum around 1 week after dosing and return to pre-administration levels by 4 weeks, with this being the rationale of the once-monthly administration of CERA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation